Gestão estratégica em clube empresas: uma proposta de framework para a tomada de decisão - Avila, Andressa Germann (2024)
The impacts of strategic management for the current football business model can promote the recognition of a model proposal based on decision-making factors. Based on the above, the general objective of the research was to propose a Framework for the strategic decision-making process in a company club. The specific objectives include: a) identifying the strategic management factors that can influence the decision-making process in a club company in Brazil; b) measure strategic management factors for decision-making in a company club; c) analyze, from the perspective of business club managers, the factors that influence the decision-making process and d) develop a Framework and guidelines for strategic decision-making in business clubs in Brazil. The development of a framework for strategic decision-making in business football clubs is essential to provide solid guidelines based on evidence (Kaplan & Norton, 1992), boosting financial sustainability and competitiveness in the sports market (Barney, 1991; Mintzberg, 1994). The study adopts a qualitative and quantitative approach. In the qualitative stage it was composed of 2 phases, being: a) a Systematic Literature Review, based on the string "Club company AND manag*" in WOS, Web Of Science and Science Direct, in the period from 2010 to 2022 where they were identified and 55 articles were considered, which were analyzed using the Iramuteq and VOSViewer software; b) the second phase consisted of semi-structured interviews based on a protocol applied to 5 club company managers in Brazil. For the quantitative stage, an electronic form was developed from RSL and Literature, which was validated with 08 experts and applied to 136 club companies with 35 responses. For data analysis, simple descriptive statistics, correlation, covariance and ANOVA were performed. The main results include: RSL reveals that more than 50% of studies focus on Europe, while 25% address strategic management and Corporate Social Responsibility. Between 2018 and 2022, there was an increase in publications, especially due to the increase in the number of clubs. The results of the interviews reveal that business clubs adopt different approaches in terms of management, strategic decision-making and leadership. In aspects of the survey research, the southeast region, led by São Paulo, is home to 33% of the country's corporate clubs; Another important characteristic is that clubs have more than 75% of organizational performance linked to management. The main factors in decision making include competitiveness, sporting performance, financial sustainability and marketing strategies. It is concluded that efficient strategic management is essential for the financial sustainability of clubs in the Brazilian sports market.